Magnetic resonance imaging relaxation time in Alzheimer’s disease - Tang, Xiang; Cai, Feng; Ding, Dong-Xue; Zhang, Lu-Lu; Cai, Xiu-Ying; Fang, Qi (Brain research bulletin, 2018)
•T1 and T2 relaxation times in brain tissue.•Applications of T1 and T2 relaxation time in AD (AD patients and mouse models).•Possible mechanisms of T1 and T2 relaxation time alterations in AD. The magnetic resonance imaging (MRI) relaxation time constants, T1 and T2, are sensitive to changes in brain tissue microstructure integrity. Quantitative T1 and T2 relaxation times have been proposed to serve as non-invasive biomarkers of Alzheimer’s disease (AD), in which alterations are believed to not only reflect AD-related neuropathology but also cognitive impairment. In this review, we summarize the applications and key findings of MRI techniques in the context of both AD subjects and AD transgenic mouse models. Furthermore, the possible mechanisms of relaxation time alterations in AD will be discussed. Future studies could focus on relaxation time alterations in the early stage of AD, and longitudinal studies are needed to further explore relaxation time alterations during disease progression.